An extracellular lipid transfer protein is relocalized intracellularly during seed germination - Pagnussat, Luciana Anabella (2012)
Plant lipid transfer proteins (LTPs) constitute a family of small proteins recognized as being extracellular. In agreement with this notion, several lines of evidence have shown the apoplastic localization of HaAP10, a LTP from Helianthus annuus dry seeds. However, HaAP10 was recently detected intracellularly in imbibing seeds. To clarify its distribution, immunolocalization experiments were performed during the course of germination and confirmed its intracellular localization upon early seed imbibitionHaAP10, a LTP from Helianthus annuus dry seeds. However, HaAP10 was recently detected intracellularly in imbibing seeds. To clarify its distribution, immunolocalization experiments were performed during the course of germination and confirmed its intracellular localization upon early seed imbibition